SPIRITUAL LEADERSHIP DAN KOMITMEN ORGANISASIONAL: PERAN MEDIASI WORKPLACE SPIRITUALITY - Wijayanti, Ariyani Wahyu; Insani, Salman Faris; Purwanto, Purwanto; Saputri, Amalia Oevina; Wibowo, Titania Jenny (MOTIVASI, 2024)
Purpose– This study examines the mediating role of workplace spirituality in the spiritual leadership influences on organizational commitment. Design/methodology– The research was carried out with a sample of 116 private employees in Indonesia and managed the survey method for the data collection technique, which employs questionnaires as the self-reported instrument. PLS uses statistical data analysis tools. Findings - The research findings indicate that spiritual leadership and workplace spirituality have a positive impact on organizational commitment. Furthermore, the results also reveal that workplace spirituality acts as a mediator in the influence of spiritual leadership on organizational commitment.